Testing Democracy’s Promise: Indigenous Mobilization and the Chilean State - Rodríguez, Patricia; Carruthers, David (European Review of Latin American and Caribbean Studies, 2008)
In the early 1990s, Chile’s restored democratic government created a new legal architecture and a new institution, the CONADI (National Corporation for Indigenous Development), in order to improve the historically distant relationship between the state and indigenous groups. To the Mapuche Indians, newly institutionalized principles of constitutional rights, self-determination, and participatory co-governance promised not just more meaningful citizenship, but resolution to longstanding claims of injustice over ancestral land and natural resource claims. This project chronicles the dilution and betrayal of this commitment. In a series of tense conflicts over land, forestry, and hydroelectric power, state officials suppressed indigenous initiatives and implanted their own policy priorities within the new institutions. This experience has deepened the divisions among state actors, private actors, and indigenous communities. Still, important reform currents persist, and Mapuche activists continue to pressure and challenge the state in creative ways. This evolving relationship between the Mapuche and the state presents a vital test of the quality of Chilean democracy.Resumen: Poniendo a prueba la promesa de la democracia: movilizaciones indígenas y el estado chilenoA principios de los años noventa, el gobierno nuevamente democrático de Chile creó una nueva arquitectura jurídica y una nueva institución, la CONADI (Corporación Nacional de Desarrollo Indígena), para mejorar las relaciones históricamente distantes entre el estado y los pueblos indígenas. Para los mapuche, principios de derechos constitucionales institucionalizados recientemente, la autodeterminación, y el cogobierno prometían no solo una ciudadanía más completa, sino también la resolución de prolongados reclamos históricos por la injusticia en cuanto a su acceso a sus tierras ancestrales y recursos naturales. Este trabajo explica la disolución y la traición de esos compromisos. En una serie de tensos conflictos sobre propiedad de la tierra y mega-proyectos forestales e hidroeléctricos, los funcionarios del estado suprimieron las iniciativas indígenas para implantar sus propias prioridades políticas dentro de las nuevas instituciones. Esta experiencia ha profundizado las divisiones entre el estado, el sector privado, y las comunidades indígenas. Sin embargo, todavía persisten importantes corrientes reformistas, y los activistas mapuche continúan desafiando y presionando al estado de maneras creativas. El desarrollo de esta relación entre los mapuche y el estado representa una vital puesta a prueba de la calidad de la democracia chilena.